2015
DOI: 10.1007/s10951-015-0445-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-scheduling algorithms for high-throughput workload execution

Abstract: International audienceThis paper investigates co-scheduling algorithms for processing a set of parallel applications. Instead of executing each application one by one, using a maximum degree of parallelism for each of them, we aim at scheduling several applications concurrently. We partition the original application set into a series of packs, which are executed one by one. A pack comprises several applications, each of them with an assigned number of processors, with the constraint that the total number of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The results extend the theoretical analyses of single-resource-type scheduling [29,2] to account for the presence of multiple resource types.…”
Section: Rigid Task Schedulingsupporting
confidence: 61%
See 3 more Smart Citations
“…The results extend the theoretical analyses of single-resource-type scheduling [29,2] to account for the presence of multiple resource types.…”
Section: Rigid Task Schedulingsupporting
confidence: 61%
“…The speedup function relates the execution time of a task to the amount of resources allocated to it, and the total area is defined as the product of execution time and resource allocation. Many prior works [2,5,22] have assumed that the speedup of a task is a nondecreasing function of the amount of allocated resources (hence the execution time is a non-increasing function) and that the total area is a non-decreasing function of the allocated resources. One example is the well-known Amdahl's law [1], which specifies the speedup of executing a parallel task with s sequential fraction using p processors as 1/(s + 1−s p ).…”
Section: Parallel Task Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work provides an important extension to our previous work on coschedules [3], which already demonstrated that sharing the platform between two or more applications can lead to significant performance and energy savings [2]. To the best of our knowledge, it is the first work to consider co-schedules and failures, and hence to use malleable applications to allow redistributions of processors between applications.…”
Section: Co-scheduling Algorithmsmentioning
confidence: 72%